Sentimento dos familiares na institucionalização de idosos - Kempp, Raquel Ingrund (2010)
This paper examines the feelings of relatives in the institutionalization of the elderly in an aged care institution. When someone decides that your elderly relative needs to go into an institution for a long stay, it does not matte the reason, there are always feelings and thoughts that will arise. It is with this concern that this research has been raised. The first question is just what are the feelings that this family experiences at the time of institutionalization. The feelings most cited and deserve attention were: deep sorrow, irreversibility of a situation, helplessness, guilt and anxiety, impotence, tranquility, admiration for the professionalism and competence. The second issue deals with the reasons that led the family to institutionalize their elderly relative and how was the decision process. The third research question asked how this family keeps their link with the elderly. When the hospitalization happens, the family not only has the right to continue holding the contact, but also the duty, since they are responsible for the institutionalization. In the fourth question we have the perception after the admission, that is, how this family realize and face the institution where the elder is leaving. It is very interesting because the coexistence makes their prejudices to be removed. The family should not be just the element who has their elderly in a nursing home, but can be a transforming agent of this site, offering suggestions and participating effectively in the day to day activities of the institution.